Improving livelihoods of smallholder upland farmers through improved and integrated cassava-based cropping and livestock systems - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This project aims to develop, together with farmers, technologies that will increase the income and improve the livelihoods of smallholder farmers living in the uplands of Lao PDR and Cambodia. This will be achieved by disseminating the selected technologies for improved cassava livestock production systems to many farmers, supporting national institutions in conducting strategic and applied research and developing procedures for monitoring the impact of new technologies on farmers’ livelihoods and the environment.